Pengaruh Loan To Deposit Ration (LDR) Dan Biaya Operasional Pendapatan Operasional (BOPO) Terhadap Return On Aseet (ROA) (Studi Pada Bank Konvensional Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2021) - Rini Widia Astuti; Abdul Hadi Sirat; Fadli Ali Taslim (Universitas 45 Surabaya, 2023)
The purpose of the study was to identify and analyze the effect of loan to deposit ratio (LDR) on operational costs operating income (BOPO) and simultaneously on return on assets (ROA). the object of this research is conventional banks listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The sample was selected by purposive sampling method with the number of banks obtained in accordance with the specified criteria as many as 42 banks. Data management techniques using multiple linear regression analysis assisted by the SPSS 25 program.The results of this study indicate that: (1) loan to deposit ratio (LDR) has no effect on return on assets (ROA) (2) operational costs operating income has a negative effect on return on assets (ROA).